Implementation Of Public Services Based On The Digides Application (Digital Village) In Pondok Kelapa District, Central Bengkulu District" - Fanro (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2024)
This research discusses the implementation of public services based on the Didiges application in the village government service and administration system. This research is based on Law no. 25 of 2009 concerning Public Services and Presidential Decree 95 of 2018 concerning Electronic-Based Government Systems. The aim of carrying out this research is to determine the extent of implementation of public services based on the Digides application, as well as the factors that influence its implementation in Tanete Rilau District. By using descriptive qualitative methods, this research produced several findings such as the quality of use of online administration features, online correspondence services, and the minimal use of mobile applications by residents. From the theory of Donald S. Van Meter and Carl E. Van Horn, it was found that the most influential factors in the implementation of Digides application-based public services in Pondok Kelapa District are policy standards and targets, resources, relationships between organizations, characteristics of implementing agents, social conditions, politics, and economics, as well as the disposition of implementers. Based on the results of the research analysis, the village government plays an important role as the front guard that serves the community more closely. Therefore, the village government should actively provide outreach regarding the use of the Digides application to the community so that digital transformation can run optimally.